2002
DOI: 10.2134/agronj2002.1305
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cotton Fiber Yield, Fiber Quality, and Soil Properties in a Southeastern Coastal Plain

Abstract: To maximize profitability, cotton (Gossypium hirsutum L.) producand As. Elms et al. (1997) reported that yield in an ers must attempt to control the quality of the crop while maximizing irrigated cotton field in Texas displayed spatial correlayield. The objective of this research was to measure the intrinsic variability present in cotton fiber yield and quality. The 0.5-ha experi-tion. These authors also noted that production of fruitmental site was located in a producer's field (Norfolk-Coxville soil ing site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 7 publications
10
57
2
3
Order By: Relevance
“…Such situation results in economical losses either due to the unnecessary application or in consequence of the imbalance among quantities of nutrients that will be available for plants Through the CV classification proposed by Wilding e Drees (1983), it was observed that pH, Ca, and V% had low variability, i.e., CV < 15%; Mn presented high variability (CV = 82.42%); and the remaining attributes were sorted as of moderate variability (15% < CV < 35%). In contradiction to what has been observed within this study, some authors have reported that the K content available for the plants presents high values for CV, while the values for the P available are normally high, remaining in the range of 40% to 80% (Johnson et al, 2002;Silva et al, 2007;Ward and Cox, 2000). Grain yield and physiological potential of seeds presented low CV, what is in accordance with what was observed by other authors, who obtained CV values varying from 8% to 29% (Pierce et al, 1995;Ping e Green, 2000).…”
Section: Resultscontrasting
confidence: 99%
“…Such situation results in economical losses either due to the unnecessary application or in consequence of the imbalance among quantities of nutrients that will be available for plants Through the CV classification proposed by Wilding e Drees (1983), it was observed that pH, Ca, and V% had low variability, i.e., CV < 15%; Mn presented high variability (CV = 82.42%); and the remaining attributes were sorted as of moderate variability (15% < CV < 35%). In contradiction to what has been observed within this study, some authors have reported that the K content available for the plants presents high values for CV, while the values for the P available are normally high, remaining in the range of 40% to 80% (Johnson et al, 2002;Silva et al, 2007;Ward and Cox, 2000). Grain yield and physiological potential of seeds presented low CV, what is in accordance with what was observed by other authors, who obtained CV values varying from 8% to 29% (Pierce et al, 1995;Ping e Green, 2000).…”
Section: Resultscontrasting
confidence: 99%
“…Dagdelen et al (2009) observed higher fiber resistance with water depth of 100% ETc, compared with other evaluated depths, and cite that fiber resistance decreases with the increase in water deficit. The same behavior was reported by Johnson et al (2002), who found positive correlation between fiber resistance and soil water availability. As to the excess of water, some studies show that fiber resistance decreases with the increase in rainfall/irrigation, which can be confirmed with the decrease in the values of fiber resistance for irrigation depths above 750 mm (105% ETc).…”
Section: Resultssupporting
confidence: 87%
“…A possible reason for the lack of spatial structure in corn oil content is that corn oil is a highly heritable trait (Weber 1987) and genetic factors have a larger impact than environmental factors (Jellum and Marion 1966). A similar phenomenon has been observed with cotton fiber properties, which are also mainly controlled by genetics (Johnson et al 2002). Corn protein content of 33Y18, starch and moisture content and test weight of both hybrids all showed moderate spatial dependence, with the percentage of spatial structure (relative to the sill or total variance) varying from 34.4 (protein, 33Y18) to 65.3% (test weight, 33G26).…”
Section: Corn Quality Parameters and Yieldmentioning
confidence: 75%
“…Johnson et al (2002) studied the spatial variability of cotton fiber quality parameters and found that many fiber length properties having strong genetic links did not exhibit any spatial correlation, while other fiber properties related to fiber maturity were spatially correlated. Kravchenko and Bullock (2002) found that soybean protein and oil concentrations exhibited well defined spatial structures, with ranges of spatial dependence exceeding 70 m in most of the study fields, although variogram parameters varied widely from field to field.…”
Section: Introductionmentioning
confidence: 99%